2019
DOI: 10.1111/wej.12463
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wastewater in sewer by Spirogyra sp. green algae: effects of light and carbon sources

Abstract: The aim of this study is to evaluate the use of Spirogyra sp. green algae for wastewater treatment process in sewer. The effects of light and carbon sources were investigated on growth of the algae Spirogyra sp, removal of nitrate, nitrite, phosphate, chemical oxygen demand (COD) and pH changes. Samples 1 & 4 were grown in autotroph form, while samples 2 & 5 and 3 & 6 were grown in media containing 100 and 200 mg/L of glucose, respectively. Samples 1 up to 3 were grown in cycling light but samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Illumination is one of the most common environmental indicators affecting algal growth [31]. Studies have shown that light sources have a very important effect on changes in spirulina growth and nitrite removal, and it was found that the growth of algae and the removal rate of nitrite level are improved under the condition of continuous illumination within a suitable range [32], which is basically consistent with the results of the algaebacteria consortia in this study. In this study, the nitrite absorption rate of the algae-bacteria consortia increased first and then decreased with the increase in illumination, even in the absence of light, the uptake rate of the algae-bacteria consortia was still high, maintaining above 0.815 µg•g −1 •h −1 .…”
Section: Illumination On Nitrite Nitrogen Uptake By the Microalgae-ba...supporting
confidence: 90%
“…Illumination is one of the most common environmental indicators affecting algal growth [31]. Studies have shown that light sources have a very important effect on changes in spirulina growth and nitrite removal, and it was found that the growth of algae and the removal rate of nitrite level are improved under the condition of continuous illumination within a suitable range [32], which is basically consistent with the results of the algaebacteria consortia in this study. In this study, the nitrite absorption rate of the algae-bacteria consortia increased first and then decreased with the increase in illumination, even in the absence of light, the uptake rate of the algae-bacteria consortia was still high, maintaining above 0.815 µg•g −1 •h −1 .…”
Section: Illumination On Nitrite Nitrogen Uptake By the Microalgae-ba...supporting
confidence: 90%
“…Nevertheless, macroalgae has been proved to remove organic chemicals by degradation and not just by bioadsorption (Khataee et al 2013). Amiri and Ahmadi (2020) showed that addition of glucose facilitated in higher COD removal from wastewater using macroalgae Spirogyra sp. than without the glucose supplement.…”
Section: Resultsmentioning
confidence: 99%
“…used for wastewater treatment are Ulva sp., Chaetomorpha sp., Oedogonium sp., Chlorophyta sp., Spirogyra sp., and Kelp sp. Macroalgae have also been shown to remove COD and BOD from several wastewaters such as municipal (Amiri and Ahmadi 2020), textile (Yaseen and Scholz 2019), piggery effluent (Nwoba et al 2017), shrimp farm waste (Santhi and Deivasigamani 2017), palm mill oil effluent (Kamyab et al 2015), and sewage (Ashokkumar et al 2019). Macroalgae have been reported to remove heavy metals due to their higher biosorption capacities; metals such as nickel, cadmium, copper, and zinc were removed by significantly synergistic action of macro-and microalgae consortium (Piccinni et al 2019).…”
Section: Emergingmentioning
confidence: 99%
“…While using this technology, the production cost can be effectively reduced to €0.70 or €0.68 per kilogramme (Negi et al 2020, Oostlander et al 2020. Arable land and high-quality irrigation are not recommended, the utilization of saltaffected or marginal land, including desert regions, along with saline or wastewater, remains a viable option and it could be used if suitable strains of algae are available (Amiri and Ahmadi 2020).…”
Section: Resultsmentioning
confidence: 99%